Pengaruh Efikasi Diri, Pemberdayaan, dan Knowledge Sharing, Terhadap Keinovatifan - Clara, Wahyuni Anjar; Entang, Muhammad; Wulandari, Dian (JURNAL MANAJEMEN PENDIDIKAN, 2024)
THE INFLUENCE OF SELF-EFFICACY, EMPOWERMENT, AND KNOWLEDGE SHARING ON INNOVATIVENESSThis study aims to determine the effect of self-efficacy, empowerment, and knowledge sharing on the innovativeness of civil servant teachers at public elementary schools in Cileungsi District, Bogor Regency. This quantitative research uses path analysis (path analysis) to test the strength of the direct and indirect influence of the independent (exogenous) variables on the dependent (endogenous) variable. The study population was all PNS teachers at Public Elementary Schools in Cileungi District, Bogor Regency, totaling 244 people, spread across 54 Public Elementary Schools in Cileungsi District, Bogor Regency. Sampling used the multistage random sample to obtain 134 people. The study concluded that there was a very significant direct positive effect on self-efficacy on innovativeness (βy1=0.377, sign0.01); there is a very significant positive effect of empowerment on innovativeness (βy2=0.184, sign0.01); there is a very significant positive effect of knowledge sharing on innovativeness (βy3 =0,325; sign0.01); there is a positive and significant direct effect of self-efficacy on knowledge sharing (βY3.1=0,353, sign0.01); there is positive direct and significant effect empowerment on knowledge sharing (βy3.2 =0,115, sign0.01). Knowledge sharing has effectively mediated the effect of self-efficacy and empowerment toward innovation. Increasing the innovativeness of elementary school teachers in Cileungsi can be improved by strengthening self-efficacy, empowerment, and knowledge sharing.